Additively manufactured biodegradable Zn metamaterials with tunable Poisson’s ratio and enhanced mechanical properties - Yixuan Shi; Jiaqi Gao; Xuan Li; Zui Tao; Chengcong Huang; Shangyan Zhao; Yuzhi Wu; Youwen Yang; Yabin Yang; Yageng Li; Lu-Ning Wang (Virtual and Physical Prototyping)
Additively manufactured (AM) biodegradable porous zinc (Zn) is a promising material for bone substitutes, with negative Poisson's ratio (NPR) metamaterials offering particular advantages due to their bone-mimicking properties and energy absorption. However, traditional NPR designs often have limited mechanical strength and have not been previously applied to biodegradable Zn scaffolds. This study introduces a novel reinforced unit cell, optimised in 3D to retain NPR characteristics while significantly enhancing scaffold strength. Using laser powder bed fusion (LPBF), we fabricated these Zn metamaterials and assessed their mechanical properties through simulations and compression tests. The optimised NPR Zn scaffolds demonstrated more uniform stress distribution, reduced stress concentration, and improved yield strength and plateau stress. Specifically, the B3 structure (porosity 61.98%) achieved an elastic modulus of 1327.17 MPa and yield strength of 15.3 MPa, matching cancellous bone requirements and showing excellent energy absorption. Permeability and in vitro immersion studies revealed that higher permeability accelerated degradation, with the B3 scaffold showing a 19.76% weight loss over 28 days and a yield strength increase of 2.3 MPa. These findings demonstrate that AM Zn metamaterials maintain NPR traits with optimised mechanical properties, positioning them as a promising concept for biodegradable bone substitutes.